Common Laboratory Parameters for Differentiating Between Community‐Acquired and Healthcare‐Associated Pneumonia. Issue 1 (27th June 2016) - Farah, Raymond; Bleier, Jonathan; Gilbey, Peter; Khamisy‐Farah, Rola
Abstract : Background and Objectives: The correct diagnosis of healthcare‐associated pneumonia (HCAP) as opposed to community‐acquired pneumonia is essential for the selection of a correct empirical antimicrobial approach, reserving the broad‐spectrum or highly potent antimicrobial therapies for resistant strains most commonly present in HCAP, whereas treating the less resistant strains, most commonly associated with community and long‐term care facility‐acquired infections, with a more targeted empirical approach. The standard approach today is to differentiate between the two based on the medical history of the past 90 days prior to admission. Measurable, quantitative assessment may be able to assist in this decision. The objective of this study is to find a measurable method of differentiating between community‐acquired and healthcare‐associated pneumonias. Materials and Methods: The records of 126 patients admitted with a diagnosis of pneumonia were divided into two groups based on the probable cause of their disease, in accordance with common practice. The routine laboratory work taken upon admittance was analyzed using logistical regression and Student's t ‐test. Results: We have found that the red blood cell distribution width and the neutrophil‐to‐lymphocyte ratio, both routine parameters obtained in a simple blood count, can each assist in differentiating between community‐acquired and healthcare‐associated pneumonias. Conclusion: We have found two statistically significant parameters that may be used as adjuncts to the medical history, chest radiography and other parameters in forming an immediate clinical impression of a patient presenting with pneumonia.